1,2,4-Triazolo-quinazolinones as Effective Antifoulants: Molecular Design, Synthesis, and Biological Evaluation - Gudala, Satish; Dong, Miao; Lin, Xinrui; Liu, Ruotong; Vinothkanna, Annadurai; Jha, Anubhuti; Sharma, Archi; Wang, Dazhuang; Liu, Xinghua; Yang, Jianxin (Langmuir, 2024)
A series of 1,2,4-triazolo-quinazolinones and 1,2-benzisothiazolone derivatives (S1–S12) were successfully synthesized as environmentally friendly alternatives to copper-based antifouling paints using N-alkylation, cyclocondensation, and one-pot three-component and amide coupling reactions. The monoclinic structure of single-crystal 1,2,4-triazolo-quinazolin-acetic acid (S8) was confirmed by single-crystal X-ray diffraction analysis. All the synthesized molecules were studied for their in silico molecular docking interactions with three target proteins, namely, RbmA, ToxR, and Bap. Following that, the antialgal activity was assessed against two types of marine algae: Chlorella sp. and Chaetoceros curvisetus. The minimal inhibitory concentration and zone of inhibition have been used to evaluate the antibacterial activities of S1–S12 against both marine Gram-positive (Staphylococcus aureus) and Gram-negative (Vibrio parahemolyticus and Vibrio vulnificus) bacteria. Additionally, antifouling studies have been done on all the compounds, and among them, 1,2,4-triazolo-quinazolinyl-acetate (S7), 1,2,4-triazolo-quinazolinyl-acetic acid (S8), 1,2,4-triazolo-quinazolinyl-oxobutanoate (S9), benzo[d]isothiazolyl butanoate (S10), benzo[d]isothiazolyl-acetic acid (S11), and 1,2,4-triazolo-quinazolinyl-acetyl-benzo[d]isothiazolone (S12) exhibited good antialgal, antibacterial, and antifouling activities.